2016
DOI: 10.1111/liv.13006
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis and management of inactive HBV carriers

Abstract: Patients with chronic hepatitis B virus (HBV) infection lacking the serum hepatitis B e antigen (HBeAg) and with antibodies against HBeAg (anti-HBe), are the prevalent subgroup of HBV carriers worldwide. The prognosis of these patients is different from inactive carriers (ICs), who are characterized by persistently normal serum alanine aminotransferase (ALT) and low (<2000 IU/ml) serum HBV DNA levels, a serological profile that may also be intermittently observed in patients with HBeAgnegative chronic hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 37 publications
0
48
1
Order By: Relevance
“…The natural course of HBV infection is associated with immunological changes that occur in three phases: tolerance, eradication, and recovery[3]. These phases are classified based on the serum aminotransferase level, hepatitis B e antigen (HBeAg) and HBV DNA titers, which represent hepatitis and viral replication, respectively[4,5]. Recovery is defined as ceasing of the self-replicating activity of the HBV genome and its transition to a non-replicating state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural course of HBV infection is associated with immunological changes that occur in three phases: tolerance, eradication, and recovery[3]. These phases are classified based on the serum aminotransferase level, hepatitis B e antigen (HBeAg) and HBV DNA titers, which represent hepatitis and viral replication, respectively[4,5]. Recovery is defined as ceasing of the self-replicating activity of the HBV genome and its transition to a non-replicating state.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery is defined as ceasing of the self-replicating activity of the HBV genome and its transition to a non-replicating state. In general, a serum HBV DNA level of below 2000 IU/mL is considered to indicate an inactive hepatitis B surface antigen (HBsAg) carrier state[3,5-7]. Once the HBV genome is inactivated, it remains inert throughout life, HBeAg becomes negative, and HBsAg is cleared in approximately 40% of patients after 25 years of follow-up[3].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies showed that ALT-adapted cut-offs do not influence TE diagnostic performance [186] and that the only variable associated with overestimation of F4 stage in CHB is moderate/severe necro-inflammatory activity without any direct correlation with transaminase level [187]. Interestingly, a Young's modulus of < 5 kPa in patients with normal ALT and low serum HBV DNA levels (< 2000 IU/ml) characterize inactive HBV carriers [188,189]. TE can be used to rule out significant fibrosis and cirrhosis in HBV inactive carriers, which is the best indication for TE in HBV.…”
Section: Transient Elastographymentioning
confidence: 99%
“…TE is useful in inactive HBV carriers to rule out fibrosis (LoE 2, GOR B) [188,189]. Strong consensus (18/0/0, 100 %) Point shear wave elastography (pSWE)…”
Section: Recommendation 22mentioning
confidence: 99%
“…Transition of immuneactive patients to an inactive state with low HBVDNA replication by the direct stimulation of HBVspecific Tcells or removal of immunosuppressive factors, may be sufficient to inhibit progression to cirrhosis or HCC. Inactive HBV carriers may not require specific treatment, because spontaneous HBsAg develops at a rate of 1% to 1.9%/year in these patients, making the development of HCC rare [82] . Therefore, an inactive HBV carrier may be regarded as in a state of functional cure (Table 1).…”
Section: Inhibitory Receptorsmentioning
confidence: 99%